If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5y + 3 = -4(2y + 3) + -3 Reorder the terms: 3 + -5y = -4(2y + 3) + -3 Reorder the terms: 3 + -5y = -4(3 + 2y) + -3 3 + -5y = (3 * -4 + 2y * -4) + -3 3 + -5y = (-12 + -8y) + -3 Reorder the terms: 3 + -5y = -12 + -3 + -8y Combine like terms: -12 + -3 = -15 3 + -5y = -15 + -8y Solving 3 + -5y = -15 + -8y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '8y' to each side of the equation. 3 + -5y + 8y = -15 + -8y + 8y Combine like terms: -5y + 8y = 3y 3 + 3y = -15 + -8y + 8y Combine like terms: -8y + 8y = 0 3 + 3y = -15 + 0 3 + 3y = -15 Add '-3' to each side of the equation. 3 + -3 + 3y = -15 + -3 Combine like terms: 3 + -3 = 0 0 + 3y = -15 + -3 3y = -15 + -3 Combine like terms: -15 + -3 = -18 3y = -18 Divide each side by '3'. y = -6 Simplifying y = -6
| -15+k=8 | | 10+13+16=4x-8 | | 15+20+25=3x-7 | | 5u+12=-9 | | 5(7+6x)=125 | | 4.5+4.1n-4.9n=-2.7 | | 184-5x=6x+19 | | 3u+20=-5u-12 | | 2(2x-3)=2x+1 | | 2x+7=5x-2 | | -7=63 | | 3x+1=2x+9 | | 2x-8=5x+12 | | 5x+4=9x-12 | | 4x+4=9x-12 | | -3y+5.6=-6y-(-21.6) | | -3x-6=30 | | y-3y+5.5=-6(y-3.6) | | x=(-24)+4 | | -7u+12=-4u | | -7u+12=-4 | | 8+2*(n*3)-5= | | 12+15w-4w=15 | | 2-17= | | 17-2= | | 5(x+6)+-3=37 | | -3(2x-3)=-6x+9 | | 17=5x-2 | | 4c=7C | | 6(c+9)=24-4c | | 6(7x+7)=7(6x+6) | | 13m+8m=42 |